The experience of using ACE inhibitors and Ca channel blockers in the treatment of hypertension in patients with renal cell carcinoma - Pasichnyk, Serhii; Gozhenko, Anatolii (Journal of Education, Health and Sport, 2022)
Renal cell carcinoma (RCC) is one of widely spread urological cancers. It is known that approximately 26% of patients with a history of kidney cancer (KC) may have concomitant coronary artery disease, hypertension, diabetes mellitus and some other systemic diseases, which may lead to nephrosclerotic changes and the development or progression of the existing CRF. The aim of the study. To study the renal function effects of ACE inhibitors (perindopril arginine) in patients with RCC, both as monotherapy and in combination with Ca channel blockers when conducting treatment of concomitant hypertension (HT). Materials and methods. The study enrolled 38 patients with RCC. All patients were diagnosed with RCC for the first time, with their cancer staged according to the TNM International Classification (Т1 N0 M0). Within a month, the use of combination therapy for kidney cancer complicated by Stage І, Degree ІІ hypertension was leading to increases in serum creatinine by 3 µmol/l and by 7 µmol/l in those patients where combination therapy was not used. In the meantime, during the same period, glomerular filtration rate reduced by 5 ml/min/1.73 m2 in patients of the first group and by 15 ml/min/1.73 m2 in patients of the second group.